2008
DOI: 10.1302/0301-620x.90b4.20050
|View full text |Cite
|
Sign up to set email alerts
|

The blood flow to the femoral head/neck junction during resurfacing arthroplasty

Abstract: We used Laser Doppler flowmetry to measure the effect on the blood flow to the femoral head/neck junction of two surgical approaches during resurfacing arthroplasty. We studied 24 hips undergoing resurfacing arthroplasty for osteoarthritis. Of these, 12 had a posterior approach and 12 a trochanteric flip approach. A Laser probe was placed under radiological control in the superolateral part of the femoral head/neck junction. The Doppler flux was measured at stages of the operation and compared with the initial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 28 publications
2
26
0
Order By: Relevance
“…One explanation for narrowing of the neck might be a compromised blood supply. There is increasing evidence that the posterior approach (most frequently used for HRA) and preparation of the proximal femur can impair the blood supply to the femoral head [2,4,6,20]. Studies comparing neck narrowing after HRA with different approaches (eg, the posterior approach and the surgical hip dislocation) would be of interest, considering that progressive neck thinning might lead to later complications.…”
Section: Discussionmentioning
confidence: 99%
“…One explanation for narrowing of the neck might be a compromised blood supply. There is increasing evidence that the posterior approach (most frequently used for HRA) and preparation of the proximal femur can impair the blood supply to the femoral head [2,4,6,20]. Studies comparing neck narrowing after HRA with different approaches (eg, the posterior approach and the surgical hip dislocation) would be of interest, considering that progressive neck thinning might lead to later complications.…”
Section: Discussionmentioning
confidence: 99%
“…Third, the use of general anesthesia or regional anesthesia may lead to differences in blood flow measurements. All patients in the study received general anesthesia, which did not deviate from previous LDF studies of the hip [1,5,22]. Only in the study by Nötzli et al [22] patients received either spinal or general anesthesia without differences in the amount of blood flow.…”
Section: Discussionmentioning
confidence: 91%
“…Concerns exist, however, about damage to the medial femoral circumflex artery (MFCA). This can occur during the surgical approach if performed through the posterior approach or damage to the superior retinacular vessels (RV), which can occur at the time of femoral head preparation regardless of the approach used [1,4,5,18,26,28].…”
Section: Introductionmentioning
confidence: 99%
“…The understanding of the anatomy of the extraosseous blood supply to the femoral head is of particular interest when conducting HRA because of its vulnerability during the procedure, especially with the most commonly used extended posterolateral approach (Gautier et al, 2000;Beaulé et al, 2006a;Beaulé et al, 2007a;Khan et al, 2007;Amarasekera et al, 2008). Several approaches have been investigated or modified in order to preserve an optimal oxygenation of the femoral head during and after the procedure.…”
Section: Neurovascular Injuriesmentioning
confidence: 99%
“…Several approaches have been investigated or modified in order to preserve an optimal oxygenation of the femoral head during and after the procedure. The direct lateral approach (Nork et al, 2005;Jacobs et al, 2008), the trochanteric flip approach according to Ganz et al (Ganz et al, 2001;Steffen et al, 2009a), and the modified posterolateral approach (Steffen et al, 2010) have all been shown to lead to less disruption of the blood flow and oxygenation of the femoral head in comparison to the extended posterolateral approach which was associated with a decrease of the blood flow, ranging from 40% to 70% (Beaulé et al, 2007a;Khan et al, 2007;Amarasekera et al, 2008). However, the consequences of the disruption of the medial femoral circumflex artery (Gautier et al, 2000;Kalhor et al, 2009), with the development of osteonecrosis, remains unproven (Freeman, 1978;Hananouchi et al, 2010) -possibly because of the variability in vascularization and/or the proposed presence of an intraosseous blood supply, which can be increased in osteoarthritic joints (Whiteside et al, 1983).…”
Section: Neurovascular Injuriesmentioning
confidence: 99%